1992
DOI: 10.3109/08923979209005402
|View full text |Cite
|
Sign up to set email alerts
|

Thymostimulin Administration Modulates Polymorph Metabolic Pathway in Patients with Chronic Obstructive Pulmonary Disease

Abstract: Several studies outline the imbalance of phagocyte functions in chronic obstructive pulmonary disease (COPD). In this regard, here, we have assessed either monocyte- and polymorphonuclear cell (PMN)-mediated chemotactic, phagocytic and killing capacities or PMN-triggered metabolic pathway in a group of COPD patients before and at different times after thymostimulin administration. Before therapy, an increase of O2-generation and a decrease of myeloperoxidase release were found in these individuals when compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Only skin reactions following injection are known side-effects [18,19], while several studies demonstrated their ability to prevent myelosuppression and infections during chemotherapy [16,25]. In our study, most adverse events could be related to the progressive tumor and subsequently deteriorating liver function of the patients.…”
Section: Discussionmentioning
confidence: 68%
“…Only skin reactions following injection are known side-effects [18,19], while several studies demonstrated their ability to prevent myelosuppression and infections during chemotherapy [16,25]. In our study, most adverse events could be related to the progressive tumor and subsequently deteriorating liver function of the patients.…”
Section: Discussionmentioning
confidence: 68%
“…Neutrophils from patients with COPD and chronic bronchitis were less able to phagocytose zymosan particles compared with neutrophils from healthy controls [59] and a later study demonstrated reduced phagocytosis of Escherichia coli [54]. However, these studies have not been universally replicated [60,61]. To date, no published studies have investigated opsonin-independent phagocytosis in COPD despite this being thought the predominant mechanism of phagocytosis in the lung [58].…”
Section: Neutrophil Phagocytosis In Copdmentioning
confidence: 85%
“…The values of lung function tests following immunotherapy overlapped those seen before therapy. This finding suggests that immunotherapy is able to slow the clinical progression of the disease [14], In our study, treated patients received thymostimulin ( 1 mg/kg/day) for 1 week followed by a dosing regimen of 1 mg/kg/week for the next 6 months. Since the cost of this approach represented a difference of approximately 100,000 pesetas (770 USS) between study groups, it would be advantageous to reduce the weekly administra tion of thymostimulin, particularly in the light of signifi cant improvements in endpoints reported in different studies in which the drug was given for a period of 3 months [19,[21][22][23],…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of the frequency and/or severity of infec tious events. days of antibiotic treatment and susceptibili ty to sudden dyspnea events has been reported in thymostiinulin-treated patients [14], This prospective random ized study was conducted to assess the effect of treatment with thymostimulin on clinical, functional and immuno logical parameters in patients with long-standing COPD during a 1-year follow-up. …”
Section: Introductionmentioning
confidence: 99%